Beyond elite law access to civil justice in America - Estreicher, Samuel; Radice, Joy (Cambridge University Press, 2016)
"This chapter by Ian Weinstein offers an overview of the body of research that describes what we know about access to civil justice for Americans of low and moderate means. It looks at the problem from two perspectives: the demand side of those who have unmet civil legal needs and the providers that offer legal assistance to this population. Weinstein evaluates surveys that attempt to quantify the civil legal needs for this population. He then reviews the body of research on how Americans fare when they represent themselves. The chapter closes with an inventory of the different civil legal service providers assisting Americans of average means, from pro bono lawyers to government-funded legal aid organizations. -Eds. The crisis in access to justice for low- and moderate-income Americans has been the subject of renewed attention by the federal government, states, and private groups in recent years"...
Keywords: LAW / General; Legal assistance to the poor -- United States; Legal aid -- United States; Rechtsbeistand; Kosten; Mittelstand; Rechtsschutz; Unterschicht; USA; Aufsatzsammlung